Scientific Article "Lesson Study": Portrait of Improving the Teacher Learning Quality - Winaryati, Eny; Iksan, Zanaton Haji; Rauf, Rose Amnah Abd; Sugiharto, Prasetyawan Aji; Fadlurohman, Alwan; Yusrin, Yusrin; Maharani, Endang Tri Wahyuni (Journal of Learning Improvement and Lesson Study, 2024)
The aim of this research is: photographing the teacher's lesson study learning process, as well as evaluate information findings resulting from LS scientific article preparation activities. This research is based on a phenomenological approach, which focuses more on phenomena that are felt, obtained, responded to, perceived by subjects (humans) towards objects (LS scientific articles) written by teachers. The results of LS teacher's writing of scientific articles, are the result of narrating the implementation of lesson study, producing several findings, namely: firstly, they have writing skills to narrate teaching experiences. Some teachers are doing this skill for the first time. Second, photographing LS activities to narrate in articles, provides an interesting and challenging experience. Third, being able to present learning activities to be published as work results is a source of pride for teachers. Fourth, considering that LS activities are personal experiences, conveying them in written form is like telling a story. Fifth, encourage collaborative writing, as a result of collaborative LS experience, and the results of collaborative work. Sixth, preparing LS articles encourages teachers to look for lots of references, so that good LS articles are produced. Seventh, articles that are prepared collaboratively produce rich ideas, because they create an exchange of ideas to produce better articles. Eighth, there is a correlation between the lesson study stages, the problems that will be solved through learning, and the learning strategies carried out by the teacher. Ninth, LS activities will become teacher best practices in learning, when written in a scientific article. This LS scientific article expands information on the success or best practice of learning for many people. Tenth, the quality of the scientific articles produced is a portrait of the mastery of the lesson study that has been carried out. Suggestion: it needs to be used as a habit for lesson study activities which have an impact on writing scientific articles. The aim is to improve writing skills for teachers, while encouraging collaborative work as a habituation process, as well as training that learning experiences can become best practices that can be disseminated as more useful information.